2007
DOI: 10.1007/s10549-007-9838-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CHEK2 FHA domain in Czech patients with sporadic breast cancer revealed distinct rare genetic alterations

Abstract: The CHEK2 gene mutations I157T (c.470T>C) and IVS2+1G>A affecting the forkhead-associated domain (FHA) have been shown to increase the risk of breast cancer development in several populations. We analyzed the CHEK2 gene segment coding for FHA domain in 673 unselected breast cancer patients and 683 controls from the Czech Republic using the denaturant high-performance liquid chromatography. The found frequency of predominant FHA alteration I157T did not differ between breast cancer patients (19/673; 2.82%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
2
24
1
1
Order By: Relevance
“…We ascertained six different CHEK2 alterations localized within FHA-coding region (c.470T>C, c.475T>C, c.542G>A) or in its proximity (IVS1-5T>A, IVS2+24C>T, IVS2-54C>T (this variant was erroneously referred to as IVS2-55C>T in our previous publications [14,17]; Table 2). The overall fre- quency of CHEK2 alterations in the group of HL patients (5.7%) differed significantly from that characterized previously [13] in controls (2.8%; p = 0.04). Presence of any alteration within analyzed region was associated with increased risk of HL development (OR = 2.11; 95% CI = 1.08 -4.13).…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…We ascertained six different CHEK2 alterations localized within FHA-coding region (c.470T>C, c.475T>C, c.542G>A) or in its proximity (IVS1-5T>A, IVS2+24C>T, IVS2-54C>T (this variant was erroneously referred to as IVS2-55C>T in our previous publications [14,17]; Table 2). The overall fre- quency of CHEK2 alterations in the group of HL patients (5.7%) differed significantly from that characterized previously [13] in controls (2.8%; p = 0.04). Presence of any alteration within analyzed region was associated with increased risk of HL development (OR = 2.11; 95% CI = 1.08 -4.13).…”
Section: Resultscontrasting
confidence: 64%
“…Except for the c.542G>A (p.R181H) mutation, all other identified alterations were previously found in Czech breast, colorectal or pancreatic cancer patients [13,14,17]. The R181H was identified in breast and prostate cancer patients from Germany [18] and the USA [19], respectively, however, this variant most likely do not interfere with the function of the CHK2 (Align GVGD: Class C0) and together with c.538C>T (p.R180C -identified in one control subject) may represent neutral CHEK2 sequence variants.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In Ile157Thr (470T>C) mutation of CHEK2 gene, it was observed that 157Thr was located in the second fork head-associated domain (FHA) of the protein and the mutation resulted into the reduction of the activity of this protein in response to DNA damage (Ahn et al, 2002). IVS2+1G"A mutation revealed abnormal splicing and it led into frame shift and synthesis of truncated protein (Kleibl et al, 2008).…”
Section: Discussionmentioning
confidence: 99%